Comparative study of awareness and practices regarding menstrual hygiene among adolescent girls residing in urban and rural area - Dabade, Kuldeep Jagannath; Dabade, Sheetal Kuldeep (International Journal Of Community Medicine And Public Health, 2017)
Background: Menstruation is still regarded as something unclean or dirty in Indian society and it is strongly related with misconceptions and cultural restrictions. Learning about hygiene during menstruation is a vital aspect of health education for adolescent girls as patterns that are developed in adolescence are likely to persist into adult life. Methods: A community based cross sectional study conducted in urban and rural field practice area of Department of Community Medicine, Khaja Banda Nawaz Institute of Medical Sciences, Gulbarga from Feb 2015 to July 2015. A total 230 adolescent girls were included in the study of which 123 from urban and 107 from rural area, after taking their verbal consent. Results: Total 163 (70.9%) adolescent girls were aware about menstruation before the attainment of menarche. Awareness in urban area 95 (77.2%) was found higher compared to rural area 68(63.5%) and this difference was found to be statistically significant (p<0.02). It has been found that 83(67.5%) study participants from urban area used sanitary napkin during menstruation compared to only 56(52.3%) from rural area and this difference found statistically significant (p<0.01). Conclusions: Overall awareness about menstruation was found low in both urban and rural area and needed to be increased by intensive health education among adolescents.